Age, Not Sex, Modifies the Effect of Frailty on Long-term Outcomes After Cardiac Surgery. Issue 4 (11th April 2022) - Sun, Louise Y.; Spence, Stewart D.; Benton, Samantha; Beanlands, Rob S.; Austin, Peter C.; Bader Eddeen, Anan; Lee, Douglas S.
Abstract : Objective: To examine the prevalence of frailty in surgical patients and determine whether age and sex modify the relationship between frailty and long-term mortality. Background: Frailty is a complex and prevalent clinical syndrome. The cardiac surgery literature consists mostly of small, single-center studies, and the epidemiology of frailty remains to be fully elucidated in a real-world surgical population. Methods: This retrospective cohort study included patients who underwent coronary artery bypass grafting, and/or aortic, mitral or tricuspid valve surgery in Ontario, Canada, between 2008 and 2016. The primary outcome was all-cause mortality. Survival probabilities were calculated using the Kaplan-Meier method, and the association of covariates with the hazard of death was assessed using multivariable Cox proportional hazard models. Frailty was assessed using the Johns Hopkins Adjusted Clinical Groups frailty-defining diagnoses indicator. Results: Of 72, 824 patients, 11, 685 (16%) were frail. At median 5 ± 2 years of follow-up, 2921 (25.0%) frail patients and 8637 (14.1%) non-frail patients had died [adjusted hazard ratio 1.60; 95% confidence interval (CI), 1.53–1.68]. The adjusted hazard ratio was highest in patients who underwent isolated mitral (2.18; 95% CI, 1.71–2.77) and mitral + aortic valve surgery (1.85; 95% CI, 1.33–2.58) and lowest after coronary artery bypass grafting + mitral valve surgery (1.38; 95% CI, 1.11–1.70). Age, but not sex, modified the effect of frailty on mortality; such that the rate of death decreased linearly with increasing patient age. Conclusions: We observed a high prevalence of frailty in patients undergoing cardiac surgery, and a statistically significant association between frailty and long-term mortality after cardiac procedures. Importantly, the rate of death was inversely proportional to age, such that frailty had a stronger adverse impact on younger patients. Our findings highlight the need to incorporate frailty into the preoperative risk stratification and investigate strategies to support younger patients who are frail.